Prevalence and severity of hypoglycemia in a sample of neonates in Erbil city - Rajab, Ahmed S.; Chalabi, Dlair A.K.; Al-Rabaty, Abbas A. (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Transient hypoglycemia may affect the newborn in the first hour of life and is the most prevalent metabolic disorder. The maternal-fetal diffusion that keeps the fetal glucose level nearly two thirds of the maternal glucose concentration. This study aimed to identify the prevalence of hypoglycemia and detect certain demographic and maternal factors that may be associated with and their relation to neonatal blood glucose level. Methods: A prospective cross-sectional study was conducted in Erbil Maternity Teaching Hospital in Erbil city during a period of 4 months, from February 1st to May 31st, 2013. A total of 400 newborns from the neonatal care unit and the delivery and waiting rooms were included in the study. All of them were less than 3 hours of age and didn’t receive oral feeding. Results: Among 400 neonates, 65 were hypoglycemic confirmed by serum sample with a prevalence of 16.25% during the first 3 hours. Most of the screened neonates were male (male: female ratio 1,45: 1). A highly significant association was found between neonatal hypoglycemia with preterm babies and hypoglycemic mother. Grand multiparity, low birth weight and head circumference also may predispose to hypoglycemia while mean length of affected babies was lower than the normoglycemic group. The severity of hypoglycemia was significantly associated with gestational age, birth weight and maternal serum glucose status. Conclusion: Hypoglycemia is present in relatively high frequency among newly born babies and certain factors like prematurity, low birth weight and maternal hypoglycemia can predict its occurrence and its severity.